Exploring Taste Through Poetic Harmony: Promotion of Malay Gastronomy on the Riau Sastra.com Portal - Piliang, Wilda Srihastuty Handayani; Erni, Erni (UIR Press, 2024)
Promotion of Malay gastronomy is an important aspect in introducing the richness of Indonesian culture to the world. In order to promote Malay culinary delights, poetry is used as a means of expression that combines the beauty of diction with the deliciousness of food. Poetry, as a form of literature, is able to evoke images, sensations and deep feelings in the souls of its readers. In this case, poetry becomes a powerful tool to describe the taste, uniqueness and history of Malay gastronomy. Promotion of Malay gastronomy in the form of poetry can also revive stories related to traditional Malay food. In poetry, legends about the origins of food or stories about typical Malay spices can be presented with strong imagination, thereby helping to enrich the reader's understanding of the history and cultural context of the food. The Riau Sastra.com portal has an important role as a medium for publishing Malay gastronomic poetry. Through this platform, poetry writers can share their works on Malay culinary themes, and readers can enjoy the beauty of poetry while expanding their knowledge of Malay culture. In conclusion, using poetry as a promotional tool for Malay gastronomy on the Riau Sastra.com Portal can be an effective way to introduce the uniqueness and deliciousness of Malay culinary delights to a wider audience. Poetry has the power to bring stories to life, describe flavors, and arouse curiosity, making it an ideal vehicle for broadening appreciation of Indonesia's culinary heritage.